2017
DOI: 10.1371/journal.pone.0182845
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the relationship between children’s motor ability, executive function and academic achievement

Abstract: Even though positive relations between children’s motor ability and their academic achievement are frequently reported, the underlying mechanisms are still unclear. Executive function has indeed been proposed, but hardly tested as a potential mediator. The aim of the present study was therefore to examine the mediating role of executive function in the relationship between motor ability and academic achievement, also investigating the individual contribution of specific motor abilities to the hypothesized medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
121
2
15

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(158 citation statements)
references
References 110 publications
20
121
2
15
Order By: Relevance
“…Maxwell's research results support the results of this study, where motor skills (agility, balance, coordination) tend to contribute significantly to the acquisition of children's movement skills [27]. There are five basic motor skills explosive strength, speed, balance, coordination and flexibility in this study [18]. The explosive strength factor has a very strong correlation with the results of repulsion.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Maxwell's research results support the results of this study, where motor skills (agility, balance, coordination) tend to contribute significantly to the acquisition of children's movement skills [27]. There are five basic motor skills explosive strength, speed, balance, coordination and flexibility in this study [18]. The explosive strength factor has a very strong correlation with the results of repulsion.…”
Section: Resultssupporting
confidence: 84%
“…Current Pearson product correlation to examine the relationships between variables. Alpha level p 5 0.05 to find explicit significance [6,18].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, Pangelinan et al (2011) showed, in typically developing children, that performance on both cognitive and motor tasks is directly related to the brain structure (i.e., gray and white matter volume) of regions governing cognition and motor behavior. Recent research has also provided evidence that motor abilities are related to cognitive performance (i.e., academic achievement) through the mediation of executive functioning ( Schmidt et al, 2017 ). Yet, as far as we are aware, research based on the Strength Model investigating the neurophysiological contributions leading to cognitive control failures over successive tasks has not considered areas of the brain responsible for motor behavior.…”
Section: Introductionmentioning
confidence: 99%
“…First, noncognitive conditions, such as motor and sensory skills have a critical role in cognitive development. [8][9][10][11] Are there studies that account for influences of motor and/or sensory impairments on the neuropsychological outcomes of epilepsy surgery in childhood? Second, a score on a cognitive test, for example, a memory score can be low because of a language problem or an intelligence score on a timed problem-solving task can be low because of low mental speed.…”
Section: Questionsmentioning
confidence: 99%